STEAM Learning Assessment in the Growth and Development of Early Childhood Literacy - I Wayan Karta; Ni Wayan Rasmini (Universitas Pendidikan Ganesha, 2022)
Assessment of children's literacy development needs to be supported by STEAM learning assessments. This study aims to analyze the application of the STEAM learning assessment in the development of early childhood literacy. This study uses an ex-post facto approach with a quantitative descriptive method of implementing STEAM learning with authentic assessment techniques. The data collection instrument was observation with a scale of 4 structured, content valid oriented; anecdote notes to record specific behaviors, and portfolios to obtain data on children's performance, knowledge, and creative skills, with three main aspects: structure, content, and holistic. Observation of learning, anecdotal notes, and analysis of work results was carried out on 20 children in group B. The data obtained was described in 5 aspects of literacy: science, technology, engineering, art, and mathematics. Literacy development is described in ordinal data and analyzed descriptively using percentage techniques. The results showed that all children developed completely regarding technological and mathematical literacy. On average, they developed very well; 90% of children developed completely in the scientific aspect, with an average development according to expectations; 60% of children developed completely in engineering literacy and 50% in artistic literacy, with an average development as expected. This research implies that the STEAM learning assessment can assist in developing early childhood literacy.